1994
DOI: 10.1063/1.357897
|View full text |Cite
|
Sign up to set email alerts
|

Study of C49-TiSi2 and C54-TiSi2 formation on doped polycrystalline silicon using in situ resistance measurements during annealing

Abstract: la situ resistance versus temperature or time for reactions between 32 and 57.5 nm of titanium and undoped or doped polycrystalline silicon (boron, arsenic, or phosphorus, 7.9X1019-3.0X1020/cm3) has been measured and no clear correlation was found between the activation energy for the formation of the industrially important low-resistance C54-TiSia phase and its formation temperature. It is also demonstrated that with certain moderate doping levels typical of complementary metal-oxide-semiconductor manufacturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Heterogeneous nucleation of C54 TiSi 2 occurs at the triple grain boundaries (grain edges) of the C49 phase [4], [8] while grain boundary nucleation has only been observed at the boundaries buried inside the film in thick titanium disilicide layers [4]. The values reported for the activation energy of the C49-C54 transformation are spread in the range between 3.3 and 6 eV depending on the details of the transformation [4], [6], [9]- [12] (single or double step annealing, substrate doping, blanket or patterned film, film thickness. .…”
mentioning
confidence: 99%
“…Heterogeneous nucleation of C54 TiSi 2 occurs at the triple grain boundaries (grain edges) of the C49 phase [4], [8] while grain boundary nucleation has only been observed at the boundaries buried inside the film in thick titanium disilicide layers [4]. The values reported for the activation energy of the C49-C54 transformation are spread in the range between 3.3 and 6 eV depending on the details of the transformation [4], [6], [9]- [12] (single or double step annealing, substrate doping, blanket or patterned film, film thickness. .…”
mentioning
confidence: 99%
“…In our experiment, however, C49 TiSi 2 grown by PECVD was not changed into C54 TiSi 2 after RTA at 900°C. It was already reported that the phase transition of C49 to C54 was incomplete on heavily doped Si substrate 9 and very narrow lines. 10 The Si substrate was heavily doped in our experiment, too.…”
Section: Resultsmentioning
confidence: 98%
“…[1][2][3][4][5][6][7] Silicides can significantly reduce the contact resistance of the gate electrode and the source/drain regions as compared to nonsilicided structures. In particular, titanium disilicide (TiSi 2 ) has been used extensively as a contact material in ultra-large-scale integration technology because of its low electrical resistivity and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 TiSi 2 is a polymorphic material and may exist either as a high resistivity (ϳ60-90 ⍀cm) base-centered orthorhombic C49 phase or a low resistivity (ϳ15-20 ⍀cm) face-centered orthorhombic C54 phase. [2][3][4] When titanium reacts with silicon, the high resistivity C49 phase forms at temperatures ranging between 550 and 650°C and then transforms into the low resistivity C54 phase at annealing temperatures greater than 650°C. The C49 structure usually forms first due to a lower barrier to nucleation that has been attributed to a lower surface energy of this phase.…”
Section: Introductionmentioning
confidence: 99%